Evolution of mechanical properties of thermal barrier coatings subjected to thermal exposure by instrumented indentation testing. Issue 8 (June 2016) - Li, C.C.; Wang, T.; Liu, X.J.; Zheng, Z.H.; Li, Q.
Abstract: The evolution of mechanical properties, namely Young's modulus, hardness, fracture toughness and residual stresses of air plasma-sprayed 8 wt% Y2 O3 -stabilized ZrO2 thermal barrier coatings (TBCs) subjected to thermal exposure at 1100 °C, was evaluated based on an instrumented indentation testing system. It is found that the variation of Young's modulus and hardness with the increase of thermal exposure time can be divided into two regimes: a rapid initial increase, followed by a more gradual increase. Conversely, fracture toughness decreased from the initial value of 1.48–1.05 MPa m 1/2 after 350 h, indicating the degradation of TBCs. And the corresponding residual stress in top coat varied from the deposition stress of −29.9 MPa to a maximum of −56.0 MPa within 100 h, and then decreased to −15.0 MPa after 350 h. The evolution of mechanical properties was correlated with microstructural changes in the top coat. Microstructure observations revealed that thermally grown oxide (TGO) formed at the interface between ceramic coat and bond coat, and was predominantly comprised of Al2 O3 layer, along with some oxide clusters of (Cr, Al)2 O3, (Co, Ni)(Cr, Al)2 O4 and NiO. The growth of TGO followed a parabolic law with a rate constant of 0.13236 μm 2 /h. After 350 h, porosity in 8YSZ coatings was reduced from 8.39% to 5.79% as a result of activated diffusion-controlled sintering.